Auf Betalaktamantibiotika bei anamnestischer „Penicillinallergie“ verzichten? - Massoth, Christina; Saadat-Gilani, Khaschayar; Wenk, Manuel (AINS - Anästhesiologie · Intensivmedizin · Notfallmedizin · Schmerztherapie, 2023)
Drug allergies are frequently reported by patients undergoing pre-anesthesia evaluation, potentially resulting in a suboptimal treatment with alternative substances. While about 10% of patients report to be allergic to penicillin, less than 1% have a true IgE-mediated allergy. Multiple factors contribute to this large prevalence, such as misinterpretations of common gastrointestinal side effects as “allergic”, a history of penicillin treatment for infectious mononucleosis resulting in skin rashes, uncritical acceptance of the diagnosis by medical staff or neglect to the fact that most patients will lose their sensitivity after 10 years. In addition to this, cephalosporins are regularly withheld from patients with penicillin allergy due to an unwarranted fear of cross-reactivity. Therefore, a correct identification of those in which penicillins or cephalosporins are truly contraindicated is paramount to avoid an unnecessary use of antibiotics with a less favorable spectrum.
Keywords: Penicillinallergie; Infektionsprophylaxe; antiinfektive Therapie; Betalaktamantibiotika-Überempfindlichkeit